APLICAÇÕES DA RESSONÂNCIA MAGNÉTICA FUNCIONAL NO DIAGNÓSTICO PRECOCE DA DOENÇA DE PARKINSON: UMA REVISÃO SISTEMÁTICA - Souza, Yasmin Silva; Grassioli, Lucas Guimarães; Tamura, Lucas Hideki Hara; Castilho, Gabriel Chamorro; Vieira, Maria Eduarda Menck; Fernandes, Ana Luiza Ferreira; Bandeira, Felipe Sieiro; de Moraes, Pietro Ferri (LUMEN ET VIRTUS, 2025)
Introduction: Parkinson disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms that typically emerge after extensive dopaminergic neuronal loss. Functional magnetic resonance imaging (fMRI) has emerged as a powerful tool for identifying early neural dysfunctions preceding overt clinical manifestations.Objective: To systematically evaluate the evidence regarding the diagnostic utility of fMRI in detecting early or prodromal Parkinson disease, highlighting the main paradigms, analytical methods, and biomarkers associated with altered brain connectivity and activity patterns.Methods: Searches were conducted in PubMed, Scopus, Web of Science, Cochrane Library, LILACS, ClinicalTrials.gov, and ICTRP. Studies published from 2019 to 2025 investigating the use of task-based or resting-state fMRI in early, prodromal, or de novo PD were included. Data extraction followed PRISMA guidelines. Methodological quality was assessed with the Newcastle-Ottawa Scale for observational studies and QUADAS-2 for diagnostic accuracy.Results and Discussion: 24 studies met the eligibility criteria. Altered functional connectivity was consistently observed within the basal ganglia–thalamocortical circuit, default mode network, and cerebellar regions. Machine-learning models using fMRI-based biomarkers achieved diagnostic accuracies between 82 % and 95 % in distinguishing early PD from healthy controls. However, heterogeneity of acquisition parameters and analytic pipelines limited direct comparability across studies.Conclusion: fMRI provides sensitive markers of early neuronal dysfunction in Parkinson disease and holds promise as a non-invasive adjunct to clinical and molecular biomarkers. Standardization of protocols and longitudinal validation are required before routine clinical implementation.